Jean Gardette (1756-1831): The Father of the American Dentistry - Riaud, Xavier (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
Jean Gardette was a French dentist. He was considered as the father of the American dentistry. His history is defined in this chapter.